A Proposed Educational Model to Improve the Operations of Knowledge-Exchange between MOE and Higher Education Institutions in Jordan - Husni Ana,am Ali Salem; "Mohammed Amin" Hamed Qudah (University of Science and Technology, Yemen, 2017)
The purpose of this study was to build a proposed educational model for improving knowledge-exchange processes between the Ministry of Education and Higher Education institutions in Jordan. The sample of the study consisted of (301) educational leaders: (158) academic staff members from the Faculty of Educational Sciences - University of Jordan - and the Faculty of Education in Yarmouk University; and (143) members from the center of Jordanian Ministry of Education for the academic year 2016/2017. To achieve the aims of the study, the researcher built a questionnaire, consisting of (88) items as tool for collecting data. The research tool was checked for its validity and reliability semantics. To analyze the data, means and standard deviation were used. The results of the study showed that the educational leaders rated the degree of practicing knowledge-exchange processes between Jordanian Ministry of Education and Higher Education institutions in Jordan as (moderate). Also, they rated the obstacles that face knowledge-exchange processes as (moderate). The study concluded with a proposed educational model for improving knowledge-exchange processes between the Ministry of Education and Higher Education institutions in Jordan, and recommended to be approved and applied in Jordan. Keywords: A Proposed educational model, Knowledge-exchange processes, Practicing degree, Obstacles, Jordanian Universities, Jordanian Ministry of Education